IL-1β knockdown inhibits cigarette smoke extract-induced inflammation and apoptosis in vascular smooth muscle cells - Hongfeng Jiang; Zhangqiang Guo; Kun Zeng; Haiyan Tang; Hanxuan Tan; Rui Min; Caihua Huang (PLoS ONE, 2023)
Objective This study was aimed to investigate the role of interleukin-1β (IL-1β) in cigarette smoke extract (CSE)-induced apoptosis in vascular smooth muscle cells and the underlying mechanism in a rat derived cell line. Methods Rat thoracic aortic smooth muscle cells (A7r5) were divided into six groups including control, CSE (model), CSE+ overexpression empty vector (OvExp-EV), CSE+IL-1β knockdown (KD), and CSE+ IL-1β knockdown empty vector (KD-EV). The mRNA expression levels of IL-1β and pregnancy-associated plasma protein A (PAPP-A) were detected by quantitative polymerase chain reaction (qPCR). The apoptosis of A7r5 cells was detected by flow cytometry. The expression levels of inflammatory mediators (TNFα, IL-6 and IL-8) and apoptotic proteins (Bax and Bcl-2) were determined by western blot. Results CSE induced significant apoptosis in vascular smooth muscle cells (P < 0.01) and elevated the mRNA levels of IL-1β and PAPP-A (P < 0.01). CSE administration increased protein expression of Bax, TNF-α, IL-6, and IL-8, with significantly reduced Bcl-2 expression (P < 0.01). IL-1β knockdown significantly decreased cell apoptosis via regulating the expression of these proteins (P < 0.05 or P < 0.01). Conclusion IL-1β is involved in CSE-induced PAPP-A expression and apoptosis in vascular smooth muscle cells, which might be considered as a target for preventing of cardiovascular diseases caused by cigarette smoking.